Correction: Downsizing the BAD BH3 peptide to small constrained α-helices with improved ligand efficiency. Issue 48 (23rd November 2016) - Shepherd, Nicholas E.; Harrison, Rosemary S.; Ruiz-Gomez, Gloria; Abbenante, Giovanni; Mason, Jody M.; Fairlie, David P.
Abstract : Correction for 'Downsizing the BAD BH3 peptide to small constrained α-helices with improved ligand efficiency' by Nicholas E. Shepherd et al., Org. Biomol. Chem., 2016, DOI: 10.1039/c6ob02185a.